PENGARUH PENGGUNAAN MODUL DAN PENGGUNAAN BUKU PAKET TERHADAP PRESTASI BELAJAR MATA PELAJARAN IPS SISWA KELAS V SDN SUKABUMI 10 - Pudji Hariati Ningsih (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2015)
This research aims to know the influence of module and printed book use toward fifth graders’ social learning achievement. The respondents were 75 student at SDN Sukabumi 10 Probolinggo, As the results, it showed that module and printed books positively influence students’ learning achievement.